A dimerization interface mediated by functionally critical residues creates interfacial disulfide bonds and copper sites in CueP - Abriata, Luciano Andres (2014)
CueP confers bacterial copper resistance in the periplasm, particularly under anaerobic conditions, through an unknown mechanism. The only available structure and limited solution data suggest that CueP forms noncovalent dimers in solution, whereas sequence conservation suggests important roles for three cysteines and two histidines as copper ligands. Here we report evidence of a dimerization equilibrium mediated by a newly identified interface of functional relevance, which occludes internal copper sites and disulfide bonds but allows for intra- and interchain disulfide bonding, an extensive disulfide relay, and interfacial copper sites. Our results suggest a role for CueP linking redox-state sensing and copper detoxification.